Reprocessing of polypropylene/cellulose composites: effects on thermal properties - Samat, Noorasikin; Sharifuddin, N; M.I, Shafiee (2019)
The reprocessing and maleic-anhydride grafted polypropylene (MAPP) coupling agent effects on the thermal properties of recycled polypropylene (rPP)/microcrystalline cellulose (MCC) composites was investigated. rPP composites with MCC loading of 5wt% and 20wt% were prepared by injection molding up to five cycles. The change in the chemical composition in the composites was monitor with Fourier transform infrared spectroscopy (FTIR). Differential scanning calorimetry (DSC) and Thermogravimetric (TGA) tests were performed to compare thermal behavior of the rPP/MCC composites at different processing cycles. Analysis of thermal behavior showed a slight increase in the melting temperature of reprocessing composites with increasing number of cycles; associated to the higher percentage of crystallinity. The thermal stability of composites is affected by the number of reprocessing cycle, temperature and MCC loadings. It is noticed that the reprocessing did not disrupt the interaction between MAPP, MCC fibers and rPP matrix